Collusion-secure and cost-effective detection of unlawful multimedia redistribution - Sebe, F.; Domingo-Ferrer, J. (IEEE transactions on systems, man and cybernetics. Part C, Applications and reviews, 2003)
Intellectual property protection of multimedia content is essential to the successful deployment of Internet content delivery platforms. There are two general approaches to multimedia copy protection: copy prevention and copy detection. Past experience shows that only copy detection based on mark embedding techniques looks promising. Multimedia fingerprinting means embedding a different buyer-identifying mark in each copy of the multimedia content being sold. Fingerprinting is subject to collusion attacks: a coalition of buyers collude and follow some strategy to mix their copies with the aim of obtaining a mixture from which none of their identifying marks can be retrieved; if their strategy is successful, the colluders can redistribute the mixture with impunity. A construction is presented in this paper to obtain fingerprinting codes for copyright protection which survive any collusion strategy involving up to three buyers (3-security). It is shown that the proposed scheme achieves 3-security with a codeword length dramatically shorter than the one required by the general Boneh-Shaw construction. Thus the proposed fingerprints require much less embedding capacity. Due to their own clandestine nature, collusions tend to involve a small number of buyers, so that there is plenty of use for codes providing cost-effective protection against collusions of size up to three.